Mental Imagery Affects Subsequent Automatic Defense Responses - Hagenaars, Muriel A.; Mesbah, Rahele; Cremers, Henk (Frontiers in Psychiatry, 2015)
Automatic defense responses promote survival and appropriate action under threat. They have also been associated with the development of threat-related psychiatric syndromes. Targeting such automatic responses during threat may be useful in populations with frequent threat exposure. Here, two experiments explored whether mental imagery as a pre-trauma manipulation could influence fear bradycardia (a core characteristic of freezing) during subsequent analogue trauma (affective picture viewing). Image-based interventions have proven successful in the treatment of threat-related disorders, and are easily applicable. In Experiment 1 43 healthy participants were randomly assigned to an imagery script condition. Participants executed a passive viewing task with blocks of neutral, pleasant and unpleasant pictures after listening to an auditory script that was either related (with a positive or a negative outcome) or unrelated to the unpleasant pictures from the passive viewing task. Heart rate was assessed during script listening and during passive viewing. Imagining negative related scripts resulted in greater bradycardia (neutral-unpleasant contrast) than imagining positive scripts, especially unrelated. This effect was replicated in Experiment 2 (N = 51), again in the neutral-unpleasant contrast. An extra no-script condition showed that bradycardia was not induced by the negative related script, but rather that a positive script attenuated bradycardia. These preliminary results might indicate reduced vigilance after unrelated positive events. Future research should replicate these findings using a larger sample. Either way, the findings show that highly automatic defense behavior can be influenced by relatively simple mental imagery manipulations.